Fe Single‐atom Sites in Two‐Dimensional Nitrogen‐doped Porous Carbon for Electrocatalytic Oxygen Reduction. Issue 14 (12th May 2022) - Wang, Yanzhi; Sun, Peng‐Fei; Zhang, Chaochao; Huang, Zhehao; Dang, Jingshuang; Liu, Xinrong; Bao, Zijia; Ma, Xiaoning; Zhang, Wei; Cao, Rui; Zheng, Haoquan
Abstract: The development of electrocatalysts for oxygen reduction reaction (ORR) is important for energy conversion devices, such as fuel cells, and metal‐air batteries. Here, we have developed a confined space strategy to prepare a two‐dimensional (2D) leaf‐like nitrogen (N)‐containing porous carbon as a single‐atom catalyst substrate. ZIF−L materials have been confined in a thin silica layer to regulate the pyrolysis. The obtained Fe single atoms doped N‐containing porous carbons (Fe SAs/N−C) maintain the 2D morphology and have Fe single‐atom active sites. Correspondingly, Fe SAs/N−C exhibits excellent ORR performance (E1/2 of 0.907 V), which is more positive than those of commercially available Pt/C (0.874 V) and most reported non‐noble metal catalysts. The durability test shows that Fe SAs/N−C exhibits good stability during electrocatalytic process. This rational design shows a new strategy to prepare 2D catalyst supports with single‐atom active sites. Abstract : Confined : A two‐dimensional (2D) leaf‐like nitrogen (N)‐containing porous carbons has been prepared and used as a single‐atom catalyst substrate. The obtained Fe single atoms doped N‐containing porous carbon (Fe SAs/N−C) exhibits excellent ORR performance (E1/2 of 0.907 V), which is more positive than those of commercially available Pt/C.